FAKTOR-FAKTOR YANG MEMPENGARUHI RETURN SAHAM PADA PERUSAHAAN PROPERTY DAN REAL ESTATE YANG TERDAFTAR PADA BURSA EFEK INDONESIA TAHUN 2009 S/D 2014 - Bambang Sudarsono, 1352020090; Sudiyatno, Bambang (Jurnal Mahasiswa Pasca Sarjana, 2015)
The aim of this study was to examine the influence of macroeconomic factors include inflation, interest rates, the exchange rate of the Rupiah against the US Dollar, as well as to examine the effect of the companys fundamentals include return on assets (ROA), debt to equity ratio (DER) and the size of the company (size) toward stock returns. The population in this study is the property and real estate companies listed on the Indonesian Stock Exchange (BEI) in 2009-2014. This research data from Bank Indonesia and the Indonesian Capital Market Directory (ICMD). Sampling using purposive sampling method, with a total sample of 104 companies. The analysis technique used to test the hypothesis is multiple regression with the results. inflation negative effect significantly on stock returns, interest rates, exchange rates and the size of the companys significant positive effect on stock returns, return on assets (ROA) negative effect is not significant to stock return and debt to equity ratio (DER) positive effect notsignificant stock returns.Keywords: inflation, interest rates, exchange rates, ROA, DER, size.